2015
DOI: 10.1002/adma.201503262
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Impact of Zinc Vacancies on Charge Separation and Charge Transfer at ZnO/Sexithienyl and ZnO/Fullerene Interfaces

Abstract: The impact of surface zinc vacancies on charge transfer and charge separation at donor/ZnO and acceptor/ZnO interfaces is identified via density functional theory calculations. The results show their effect to be related to the stronger internal electric field present near these vacancies. Thus, such surface defects can have a significant negative impact on the performance of hybrid solar cells using ZnO as electron acceptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…From Fig. 4A, it can be observed that ZIS-200 and ZIS-180 possessed a similar electron paramagnetic resonance (EPR) signal ( g = 2.003), corresponding to the electrons captured by Zn-defects 40. The difference in the EPR signal intensity indicates that ZIS-200 had an obviously higher concentration of Zn-defects than ZIS-180.…”
Section: Resultsmentioning
confidence: 95%
“…From Fig. 4A, it can be observed that ZIS-200 and ZIS-180 possessed a similar electron paramagnetic resonance (EPR) signal ( g = 2.003), corresponding to the electrons captured by Zn-defects 40. The difference in the EPR signal intensity indicates that ZIS-200 had an obviously higher concentration of Zn-defects than ZIS-180.…”
Section: Resultsmentioning
confidence: 95%
“…Δ U represents the electrostatic potential energy difference crossing a distance Δ d , the black arrow indicates the direction of the IEF. Reproduced with permission [39 . ] Copyright 2016, Wiley‐VCH.…”
Section: Qualitative and Quantitative Characterizations For Ief Deter...mentioning
confidence: 99%
“…As we have previously noted, the charge separation efficiency in the case of charge transfer from the organic to the inorganic material in most reported hybrid heterojunctions is very low, which has been attributed to various phenomena including the competing formation of triplet states, [ 47 ] trap states at the metal oxide interface, [ 48–50 ] and high geminate recombination rates of CT excitons at chalcogenide/polymer interfaces. [ 12,51 ] Figure 1C shows the measured EQE and the internal quantum efficiency (IQE) calculated therefrom using a transfer matrix model for a CuSCN/ITIC device and a PEDOT:PSS/ITIC device, with a 30 ± 5 nm ITIC layer in both cases.…”
Section: Origin Of Charge Generationmentioning
confidence: 99%
“…the high dielectric constant and delocalization of free carriers in the crystalline inorganic material might contribute to reducing the free energy that is necessary to efficiently dissociate chargetransfer (CT) excitons at inorganic/organic heterojunctions and that higher open-circuit voltage (V oc ) can therefore be achieved for a given optical bandgap in photovoltaic (PV) devices. [4,8] In practice, however, hybrid-heterojunction solar cells and photodetectors have not reached the expected performance, [1,4,[8][9][10][11][12][13][14] especially compared to their all-organic heterojunction counterparts. [15] A major limitation has been poor efficiency of photoexcited charge transfer from the organic to the inorganic material and subsequent charge separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation